2022
DOI: 10.3390/s22020501
|View full text |Cite
|
Sign up to set email alerts
|

A Fully Implantable Miniaturized Liquid Crystal Polymer (LCP)-Based Spinal Cord Stimulator for Pain Control

Abstract: Spinal cord stimulation is a therapy to treat the severe neuropathic pain by suppressing the pain signal via electrical stimulation of the spinal cord. The conventional metal packaged and battery-operated implantable pulse generator (IPG) produces electrical pulses to stimulate the spinal cord. Despite its stable operation after implantation, the implantation site is limited due to its bulky size and heavy weight. Wireless communications including wireless power charging is also restricted, which is mainly att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
(40 reference statements)
0
13
0
Order By: Relevance
“…LiCoPO4 (LCP) is another substrate material prevalently used to isolate bio-tissues from the implants. Clinical trials have confirmed the effectiveness of pain inhibition and decreased voltage overshoot brought by LCP-based SCS, opening new avenues for developing a smaller spinal cord stimulator with equivalent performance [10].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…LiCoPO4 (LCP) is another substrate material prevalently used to isolate bio-tissues from the implants. Clinical trials have confirmed the effectiveness of pain inhibition and decreased voltage overshoot brought by LCP-based SCS, opening new avenues for developing a smaller spinal cord stimulator with equivalent performance [10].…”
Section: Discussionmentioning
confidence: 96%
“…Although the pain-generating mechanism is convoluted and constitutes an enormous obstacle to the widespread use of SCS, numerous advances in SCS have been made in recent years, which include novel stimulation modalities such as high-frequency burst spinal cord stimulation (Burst-SCS) and high-frequency SCS (HF-SCS) [7], novel techniques such as dorsal root ganglion stimulation (DRG-SCS) [5] and closed-loop evoked compound action potential SCS (ECAP-SCS) [8], and technological development such as wireless power transfer [9] and emerging electrode materials [10]. As deeper rules of pain inhibition are revealed and new stimulation technologies are developed and approved, SCS no doubt has a bright prospect.…”
Section: Introductionmentioning
confidence: 99%
“…While LCs have not yet been approved to be applied as human implants, some recent research has suggested the potential of LCPs in this area due to their well‐defined mechanical properties and low moisture absorption. [ 252 ] These potential biomedical implants are compatible with the surrounding tissues, meanwhile maintaining material performances. At present, research on LCPs in the field of implantable devices mainly focuses on implantable load‐bearing scaffolds and the packaging materials for biomedical microelectrodes.…”
Section: Biomedical Applications Of Lc Materialsmentioning
confidence: 99%
“…In recent years, numerous studies have demonstrated the beneficial effects of administering appropriate electrical stimulation to humans, such as for treating diseases, reducing pain, and replacing the function of existing nerves [ 1 , 2 , 3 , 4 ]. To provide a glimpse into the ongoing research on electrical stimulation, we introduce several examples of spinal cord stimulation and retina prosthesis research.…”
mentioning
confidence: 99%
“…To provide a glimpse into the ongoing research on electrical stimulation, we introduce several examples of spinal cord stimulation and retina prosthesis research. Yun S. et al developed a fully implantable, miniaturized spinal cord stimulator based on liquid crystal polymers (LCPs) for pain control, which addresses the bulky size and heavy weight limitations of the existing implantable pulse generators (IPGs) used for spinal cord stimulation [ 1 ]. Experimental testing conducted by implanting the developed system into mice has revealed that it outperforms previous systems in terms of pain suppression efficacy.…”
mentioning
confidence: 99%